THE COUNTER-MAJORITARIAN FRAMEWORK OF HUMAN RIGHTS THROUGH THE LENS OF RENÉ GIRARD'S ANTHROPOLOGY (Journal of Teleological Science, 2026)
This article investigates the counter-majoritarian structure of human rights and the Judiciary from the perspective of René Girard's mimetic anthropology and contemporary critical theory. It questions the classical rationalist paradigm that interprets the social contract and the state monopoly on violence as pure pacts of reason, suggesting, by contrast, their historical connection to archaic sacrificial mechanisms of violence containment. Stemming from the epistemological rupture inaugurated by the Christian revelation — which unveils the injustice of majority persecution movements and establishes the episteme of the victim —, modernity comes to possess an anti-sacrificial sensitivity that overdetermines its secular institutions. Methodologically supported by bibliographic research and interpretive analysis, this work examines the judgment on same-sex unions by the Supreme Federal Court (ADI 4277 / ADPF 132) as a paradigmatic case of this institutional transmutation. It concludes that human rights act as barriers designed to prevent the closure of democratic consensus into persecutory unanimities.
Keywords: Human Rights; Counter-majoritarian structure; René Girard; Episteme of the victim; Overdetermination; ADI 4277/ADPF 132